Pengaruh Job Insecurity, Kepuasan Kerja dan Stres Kerja Terhadap Turnover Intention dengan Komitmen Organisasi Sebagai Variabel Intervening pada PT Lumina Packaging - Eki Wulanfitri; Sumartik Sumartik; Lilik Indayani (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to examine the Influence of Job Insecurity, Job Satisfaction and Job Stress on Turnover Intention with Organitational Commitment as Intervening Variable.This research uses a quantitive approach with a survey method. The sampling technique uses simple random sampling. The population in this study amounted 291 employees and the sample used amounted 75 employees of PT Lumina Packaging. Technical data analysis using Partial Least Squares (PLS) with Warppls 5.0 software. The result of this research found that Job Insecurity have a direct and significant effect on Turnover Intention by 28%, Job Satisfaction have a direct and significant effect on Turnover Intention by 41%, Job Stress have a direct and significant effect on Turnover Intention by 19%, Job Insecurity have a direct and significant effect on Organitational Commitment by 24%, Job Satisfaction have a direct and significant effect on Organitational Commitment by 19%, Job Stress have a direct and significant effect on Organitational Commitment by 20%, and Organitational Commitment have a direct and significant effect on Turnover Intention by 23%. Job Insecurity have an indirect effect on Turnover Intention through Organitational Commitment as an intervening variable by 47%, Job Satisfaction have an indirect effect on Turnover Intention through Organitational Commitment as an intervening variable 42%, Job Stress have an indirect effect on Turnover Intention through Organitational Commitment as an intervening variable by 43%.